Assessing Landscape Plant Functions for Sustainable Botanical Garden Management: (A Case Study of Enrekang Botanical Garden) - Ari, Sandri Fesly; Rahim, Iradhatullah; Yunarti (Edupedia Publisher, 2025)
Botanical gardens play a strategic role in integrating ecological, spatial, and socio-cultural functions within sustainable agricultural landscapes. This study assesses the functional performance of landscape plants in Enrekang Botanical Garden, focusing on Taman Monumen La Tinro and Taman Wangi, to support sustainable garden management. A mixed-method approach was employed, combining field observations, visual landscape documentation, and visitor perception surveys. Five functional variables were evaluated: ecological, shading, spatial, aesthetic, and conservation functions. The results indicate that aesthetic and spatial functions received the highest visitor ratings in both sites, reflecting effective visual organization and spatial clarity of planting design. Shading and conservation functions showed moderate performance, while ecological functions were perceived as comparatively weaker, suggesting limited recognition of ecological services by visitors. Comparative analysis reveals functional differentiation between the two gardens, influenced by layout configuration and vegetation composition. These findings highlight a functional imbalance between visual-spatial dominance and ecological-conservation roles. The study contributes novelty by integrating visitor-based functional assessment into botanical garden landscape evaluation, offering an applied framework to enhance sustainable, multifunctional landscape management in integrated agricultural systems.